Multi-Objective Robustness of Integrated Energy System Considering Source-Load Uncertainty - LI Jianlin, ZHANG Zedong, LIANG Ce, ZENG Fei (Shanghai Jiaotong Daxue xuebao)
Under the construction of a new power system, the integrated energy system with electricity-thermal-hydrogen interconnection will become one of the important development directions, but its whole life cycle operation economy and energy supply reliability are affected by the initial equipment capacity and daily operation scheme of the system. Therefore, a multi-objective two-stage robust optimization method is proposed, taking into account the source-load uncertainty. A grid-connected electric-thermal-hydrogen operation model including fuel cells and electrolytic cells is developed, and the source-load uncertainty is added by using the hierarchical Latin hypercube sampling and Euclidean distance scenario reduction methods, and solved by a two-stage robust optimization algorithm. The results show that the proposed method can effectively mitigate the impact of source-load uncertainty on the configuration and operation planning of the integrated energy system, which is expected to provide new ideas for the construction and operation of integrated energy systems in the future.